2015
DOI: 10.1007/s00441-015-2254-0
|View full text |Cite
|
Sign up to set email alerts
|

Transient up- and down-regulation of expression of myosin light chain 2 and myostatin mRNA mark the changes from stratified hyperplasia to muscle fiber hypertrophy in larvae of gilthead sea bream (Sparus aurata L.)

Abstract: Hyperplasia and hypertrophy are the two mechanisms by which muscle develops and grows. We study these two mechanisms, during the early development of white muscle in Sparus aurata, by means of histology and the expression of structural and regulatory genes. A clear stage of stratified hyperplasia was identified early in the development of gilthead sea bream but ceased by 35 dph when hypertrophy took over. Mosaic recruitment of new white fibers began as soon as 60 dph. The genes mlc2a and mlc2b were expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…This coincides with the upregulation of MLC gene expression observed in the white muscle of rainbow trout (58) and zebrafish (70) under sustained swimming. Very recently, this molecule has been related to the intensive stratified formation of new fibers during muscle growth in larvae of gilthead sea bream (38). Moreover, in concordance with previous studies, it has been suggested that MLC2A is more involved in larval growth (mainly hyperplasic growth) whereas MLC2B is more related to the hypertrophic growth that takes places in the adult stages (39,67).…”
Section: Discussionsupporting
confidence: 73%
“…This coincides with the upregulation of MLC gene expression observed in the white muscle of rainbow trout (58) and zebrafish (70) under sustained swimming. Very recently, this molecule has been related to the intensive stratified formation of new fibers during muscle growth in larvae of gilthead sea bream (38). Moreover, in concordance with previous studies, it has been suggested that MLC2A is more involved in larval growth (mainly hyperplasic growth) whereas MLC2B is more related to the hypertrophic growth that takes places in the adult stages (39,67).…”
Section: Discussionsupporting
confidence: 73%
“…Concerning muscle structural components, mlc2a and mlc2b showed an inverse profile, with mlc2a expression not changing with fasting but showing a significant increase at 24 h refeeding to return to basal levels at day 7. Bower and Johnston 37 also found in Atlantic salmon an increase of mlc2 after 14 days of refeeding, and previous studies in gilthead sea bream 22,23,54 showed that an increase in specifically, mlc2a expression, indicates a condition that favors muscle proliferation. In this sense, in the present study the mlc2a peak at 24 h refeeding paralleled the tendency to enhance the expression of pax7, pcna, tor and the MRFs involved in early myogenesis (myod2 and myf5), facilitating the muscle to grow during this period of compensatory growth.…”
Section: Discussionmentioning
confidence: 53%
“…The exact role of fibrillar collagens during muscle development in vertebrates is unclear. It is thought that the lateral and dorsoventral ends of the dermomyotome are a source of muscle fibers for secondary myogenesis, also known as stratified hyperplasia, and that these muscle fibers will have a distinct composition compared to the primary myofibers ( Barresi et al, 2001 ; Georgiou et al, 2016 ; Chu et al, 2018 ). The presence of specific collagens in the medial or lateral domains of the dermomyotome indicate that, by these developmental stages, they are likely beginning to differentiate between the dermis and these secondary muscle fibers.…”
Section: Discussionmentioning
confidence: 99%